The Bomber Mafia : a dream, a temptation, and the longest night of the second World War - Gladwell, Malcolm, 1963- (New York : Little Brown and Company, 2021)
Malcolm Gladwell weaves together the stories of a Dutch genius and his homemade computer, a band of brothers in central Alabama, a British psychopath, and pyromaniacal chemists at Harvard to examine one of the greatest moral challenges in modern American history.
Introduction: "This isn't working. You're out." -- Part one: The dream. "Mr. Norden was content to pass his time in the shop." ; "We make progress unhindered by custom." ; "He was lacking in the bond of human sympathy." ; "The truest of the true believers." ; "General Hansell was aghast" -- Part two: The temptation. "It would be suicide, boys, suicide." ; "If you, then, will worship me, it will all be yours." ; "It's all ashes--all that and that and that." ; "Improvised destruction." -- Conclusion: "All of a sudden the Air House would be gone. Poof."
Includes bibliographical references (pages 211-231) and index.
Keywords: World War, 1939-1945 -- Aerial operations, American; World War, 1939-1945 -- Japan -- Aerial operations, American; Bombing, Aerial -- Japan -- History -- 20th century; Aeronautics, Military -- History; Precision bombing. -- History; History